2002
DOI: 10.1128/jcm.40.10.3802-3804.2002
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Borrelia burgdorferi Sensu Lato, Tick-Borne Encephalitis Virus, and the Human Granulocytic Ehrlichiosis Agent in Ixodes persulcatus Ticks from Western Siberia, Russia

Abstract: PCR assays were used to test adult Ixodes persulcatus ticks from Western Siberia, Russia, for Borrelia burgdorferi sensu lato, tick-borne encephalitis virus (TBEV), and the human granulocytic ehrlichiosis (HGE) agent. Of the 150 ticks that were studied, 38% were infected with B. burgdorferi, 46% were infected with TBEV, and 8% were infected with the HGE agent. These three pathogens were distributed in the ticks independently of one another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…A. phagocytophilum infectious prevalence in ticks reported herein was very similar to the HGA infectious rate in ticks from some areas of Russia, ranging from 1 to 8% (Alekseev et al 2001;Morozova et al 2002). On the other hand, the HGA prevalence in questing Ixodes ticks reported from area near capitol town of Bulgaria has been shown to be higher (19.8%) (Christova et al 2001), what perhaps relates to the type of habitat and competent reservoir hosts.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A. phagocytophilum infectious prevalence in ticks reported herein was very similar to the HGA infectious rate in ticks from some areas of Russia, ranging from 1 to 8% (Alekseev et al 2001;Morozova et al 2002). On the other hand, the HGA prevalence in questing Ixodes ticks reported from area near capitol town of Bulgaria has been shown to be higher (19.8%) (Christova et al 2001), what perhaps relates to the type of habitat and competent reservoir hosts.…”
Section: Discussionsupporting
confidence: 70%
“…Low infectious prevalence of A. phagocytophilum and B. burgdorferi s.l. mixed infections has been detected in ticks from western Siberia, Russia (6%) (Morozova et al 2002) and eastern Slovakia (5%) (Derdá ková et al 2003b). We have similarly detected co-infections of both pathogens in 2.5% of tested ticks only, what indicates that these bacteria are independently distributed within tick population.…”
Section: Discussionmentioning
confidence: 96%
“…Strains described in this manuscript are shown in bold letters and are underlined. (5,15). All 4 strains of B. afzelii studied were found to be identical based on the ospA gene comparison in spite of the quite different regions of the strains' isolation.…”
Section: Discussionmentioning
confidence: 80%
“…However, in a study of coinfection rates in Ixodes persulcatus in north-eastern Europe, the two pathogens exhibited mutually exclusive distribution, which suggests that they might circulate in nature in divergent ways, which would further reduce the risk of co-infections in humans [31]. However, another study of the same tick vector indicated no interaction between TBEV and A. phagocytophilum, though results were based on limited material [32]. Additional data will be needed to evaluate the 'entomological risk' of TBEV and A. phagocytophilum co-infections more objectively.…”
Section: Discussionmentioning
confidence: 90%